(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we introduce the notion of a new class of Paradistributive latticoids termed -PDLs and investigate its properties. In addition, we prove that a Paradistributive latticoid(PDL) is a -PDL iff /θ is a Boolean algebra with a minimal element, where θ ={(,) × []^=[]^} is a congruence relation on . Further, we explore the concept of dense elements in a PDL and characterize -PDL in terms of dense elements. Also, we introduce the notion of a disjunctive PDL and we give equivalent conditions for a -PDL to be a disjunctive PDL.